Dr. İnci Ayan Birol'un sanatı ve Türk Bezeme Sanatına katkıları - Kivi, Nur Nevin Azeimnezhad (My University, 2022)
DR. İNCİ AYAN BİROL’UN SANATI VE TÜRK BEZEME SANATLARINA KATKILARI Türk Bezeme Sanatları’nda özel bir yere sahip olan Dr. İnci Ayan Birol, önemli bir sanatkâr ve eğitimcidir. Aynı zamanda eğitim alanında yapmış olduğu hizmetleri incelendiğinde bu yönüyle de dikkate değerdir. İstanbul Üniversitesi Fen Fakültesi Fizik-Matematik Bölümü’nde okurken, sanat eğitimini de aynı paralellikte yürütmüştür. Cumhuriyet döneminin çok değerli şahsiyetleri olan, Ord. Prof. Dr. Süheyl Ünver’den (1958-1970), Muhsin Demironat’ dan (1974-1983) ve Rikkat Kunt’ dan (1976-1985) yılları arasında tezhip dersleri almıştır. Marmara Üniversitesi’nden gelen teklif üzerine, 1988 yılında Güzel Sanatlar Fakültesi Geleneksel Türk El Sanatları Bölümü Tezhip-Minyatür Anasanat Dalı’na öğretim görevlisi olarak atanmış ve 2000 yılında emekli olmuştur. Selçuk Üniversitesi’nde Geleneksel Türk Sanatları Bölümü kurucu üyeliğinde de bulunan Dr. İnci A. Birol, lisans ve yüksek lisans derslerini, 12 yıl devam ettirmiştir. Üniversite bünyesinde birçok öğrenci yetiştirmiş usta-çırak usulünde de çok sayıda sanatkârın eğitimine katkıda bulunmuştur. XVI. yüzyıl klasik dönemin sanat anlayışı çerçevesinde, sanatımızı yaşatmak, yenilikçi yorumlarla günümüz sanatının biçimlenmesinde ve geleceğe taşınması noktasında, Dr. İnci A. Birol’un katkıları yadsınamaz. Eserlerde millî ve ferdî kimliğin bulunması gerektiğini dile getirmekte, gelenek kavramının üzerinde özellikle durmaktadır. Kültür ve sanat adına yapmış olduğu tüm çalışmaları bir amaç doğrultusundadır. Türk sanatı, Türk bezeme sanatları, teknikleri ve eğitimi üzerine çok sayıda kitap, makale ve bildirileri bulunan Dr. İnci Ayan Birol’un sanatına olan aşkı, bağlılığı ve sanatına yapmış olduğu katkılarıyla, Türk bezeme sanatlarında özel ve ayrıcalıklı bir yere sahip olmuştur

DR. İNCİ AYAN BİROL’S ART AND CONTRIBUTIONS TO TURKISH DECORATIVE ART Dr. İnci Ayan Birol has a special place in Turkish Decorative Art as Artist and educator.The services in the field of education She has done are also remarkable in this aspect. While studying at Istanbul University, Faculty of Science, Department of Physics and Mathematics, she carried out her art education in the same parallel. Birol took illumination lessons from Ord. Prof. Dr. Süheyl Ünver (1958-1970), Muhsin Demironat (1974-1983) and Rikkat Kunt (1976-1985), who were valuable personalities in Republican period. She started teaching physics in 1967 and served for 16 years at the Secondary Education and Higher Technical Teacher Training School (Marmara University Faculty of Education). With of the proposal of Marmara University, Birol was appointed as a lecturer to the Faculty of Fine Arts in 1988 and continued for 12 years in the Illumination-Miniature Department of the Department of Traditional Turkish Handicrafts, which was established in 1982, and retired in 2000. Dr. İnci A. Birol is also a founding member of the Department of Traditional Turkish Arts at Selçuk University, continued, her undergraduate and graduate courses for 12 years between Istanbul and Konya. She contributed to the education of many craftsmen in the master-apprentice manner. Birol’s contributions of the XVI century classical period, cannot be denied in keeping Turkish art alive, shaping today’s art with innovative interpretations and carrying it to the future. She indicates that national and individual identity should be present in the works and emphasizing the concept of tradition. The intellectuality relationship between meaning and art and simplicity is felt in all the works of İnci A. Birol. Apart from illumination and miniature works, she also has oil paintings, watercolor works applied in different fields and techniques. All her works in the name of culture and art are in line with a purpose. She has numerous books, articles and papers on Turkish art, Turkish decorative arts, techniques and education, has a special and privileged place in Turkish decorative arts with her love, devotion and contributions to her art.
Keywords: 21. yy; 21st century; Art, Turkish; Dr. İnci Ayan Birol; Illumination; İnci Ayan Birol, 1942-; miniature; minyatür; Sanat, Türk; tezhip; Turkis Decoration Arts; Türk Bezeme Sanatları